The relationship between stress, coping, emotional intelligence, job search behaviour, and psychological well-being : a study on involuntary job loss in Indonesia - Liza Adyani (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Involuntary job loss is one of the most stressful life events that the emotional impacts can be as much as losing someone due to death. Involuntary job loss has been found to be associated with a variety of negative physical and psychological outcomes such psychological well-being. This study examines the relationship between stress, coping, emotional intelligence, job search behaviour and psychological well-being in three specific areas in Indonesia. A total of 402 individuals who have been unemployed for more than three months to four years were recruited as participants using purposive sampling method. Using three modes of questionnaires (i.e. paper-based questionnaire, online survey and online market survey platform), the participants answered questions from six established scales that measured stress, coping (i.e. problem-focused coping and emotion-focused coping), emotional intelligence, job search behaviour and psychological well-being (life satisfaction and psychological distress). It was hypothesised that: i). there is negative relationship between stress and psychological well-being; ii). emotional intelligence and job search behaviour moderate the relationship between stress and psychological well-being, and iii). coping mediates the relationship between stress and psychological well-being. Confirmatory Factor Analysis was first conducted to find underlying factors for each variable. Results from Structural Equation Modelling (SEM) were supported hypothesis that most of the predictors and criterion were significantly correlated. However, using hierarchical multiple regression to test moderating effect, only a few support was found for the moderating effects of job search behaviour and emotional intelligence. Active job search behaviour (AJSB) was moderated the relationship between stress and life satisfaction as well as social dysfunction. Preparatory job search behaviour (PJSB) only moderated the relationship between stress and life satisfaction. And finally, results from SEM using bootstrapping technique also revealed that problem-focused coping (PFC) was found to partially mediate the relationship between perceived coping with social dysfunction and anxiety while emotion-focused coping (EFC) was partially mediated the relationship between perceived coping with life satisfaction and social dysfunction. The implications of these findings are discussed, and recommendations for future research are provided.